IMPACT OF GHOST KITCHEN TOWARDS CONSUMER BEHAVIORAL INTENTION DURING MOVEMENT CONTROL ORDER - Mohd Syafiq Othman; Norfezah Md Nor; Wan Noramira Wan Rosdi (Journal of Islamic, Social, Economics and Development, 2021)
The coronavirus pandemic is likely to permanently change dining habits of Asianconsumers, particularly Malaysian Consumer, where a Ghost Kitchen or Cloud Kitchen orVirtual kitchen is becoming their main preference. Therefore, the purpose of this study is todetermine the consumers’ behavioral intention to use ghost kitchen service based ondecomposition of e-selfqual theory based. A quantitative research methodology via onlinesurvey was performed. A nonprobability sampling technique of 200 valid respondents’answered the survey. The data was then, analysed using SPSS version 21. The multipleregression result showed that more than 62% of perceived control, convenience and servicefulfilment influenced the consumers toward ghost kitchen usage. Thus, the result may serve asa groundwork for creating guideline for ghost kitchen set up and operation among foodbusinesses. Moreover, this fulfilling the research gap which is crucial in strengthening foodbusinesses’ economy in the post COVID-19 challenges.